Langerhans cells promote early germinal center formation in response to Leishmania‐derived cutaneous antigens. Issue 10 (October 2014) - Zimara, Nicole; Florian, Christian; Schmid, Maximilian; Malissen, Bernard; Kissenpfennig, Adrien; Männel, Daniela N.; Edinger, Matthias; Hutchinson, James A.; Hoffmann, Petra; Ritter, Uwe
<x xml:space="preserve">Abstract</x> Efficient formation of early GCs depends on the close interaction between GC B cells and antigen‐primed CD4+ follicular helper T cells (TFH). A tight and stable formation of TFH/B cell conjugates is required for cytokine‐driven immunoglobulin class switching and somatic hypermutation of GC B cells. Recently, it has been shown that the formation of TFH/B cell conjugates is crucial for B‐cell differentiation and class switch following infection with Leishmania major parasites. However, the subtype of DCs responsible for TFH‐cell priming against dermal antigens is thus far unknown. Utilizing a transgenic C57BL/6 mouse model designed to trigger the ablation of Langerin+ DC subsets in vivo, we show that the functionality of TFH/B cell conjugates is disturbed after depletion of Langerhans cells (LCs): LC‐depleted mice show a reduction in somatic hypermutation in B cells isolated from TFH/B cell conjugates and markedly reduced GC reactions within skin‐draining lymph nodes. In conclusion, this study reveals an indispensable role for LCs in promoting GC B‐cell differentiation following cutaneous infection with Leishmania major parasites. We propose that LCs are key regulators of GC formation and therefore have broader implications for the development of allergies and autoimmunity as well as for future vaccination strategies.